Forging a New Paradigm: On the Structure of the Interdisciplinary and its Application - Shorkend, Daniel (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
This article has three sections. In section one, I define my terms which leads to an outline of what this New Paradigm is. In section two, I develop this paradigm and suggest a visualization of it, a structure as it were. This will assist in a more thorough understanding of such a paradigm. Theoretical speculations and modelling aside or rather avoiding a “purely” philosophical bias, I then apply this model to an example culled from art and aesthetics, yet involving, in line with this New Paradigm, other disciplines such as science and sport in order to exemplify or perhaps prove my argument, by virtue of the “mixture” or inter-disciplinary framework as applied to several different variables. This section forms the bulk of the article as such an application concretizes the theoretical framework in specific ways so that the reader will ascertain the usefulness of such a venture, which in turn ought to spur and spawn future research.